Effects of Absence Defect on Criminal Procedures - Rghad Abbas Gareed; Hayder Ars Afan (Periodica Journal, 2023)
This research deals with the destructive effect of the lack of procedural defect, as it is a defect that ends the entire procedural bond, so it destroys all penal procedures, and therefore it has another effect related to the first, which is the rebound effect as a natural result of this defect, as it leads to a rebound effect on the previous procedure and the subsequent procedure, and that these effects are final effects that cannot be corrected. Therefore, the defect of non-existence is described as a defect with a permanent effect in the procedural scope, and therefore it affects the systems related to the criminal case, including the civil case.
Keywords: Criminal procedures; Legislative shortcoming; Iraqi legislator